(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research examines the contributions of major corporations—ITC Ltd., Amul Dairy, Nestle, PepsiCo, and Coca-Cola India—toward the United Nations’ 17 Sustainable Development Goals (SDGs). Through qualitative analysis, the study maps their business operations and sustainability initiatives to specific SDGs. ITC Ltd.’s Mission Sunehra Kal, Amul Dairy’s farmer empowerment programs, and the initiatives of Nestle, PepsiCo, and Coca-Cola India in responsible production, water stewardship, and climate action are analyzed for their contributions to poverty reduction, food security, gender equality, and environmental sustainability. Suggestions include enhanced collaborations, innovation in sustainable practices, and expanded use of renewable energy.